Structural basis for metal ion transport by the human SLC11 proteins DMT1 and NRAMP1 - Márton Liziczai; Ariane Fuchs; Cristina Manatschal; Raimund Dutzler (Nature Communications)
Abstract Iron and manganese are essential nutrients whose transport across membranes is catalyzed by members of the SLC11 family. In humans, this protein family contains two paralogs, the ubiquitously expressed DMT1, which is involved in the uptake and distribution of Fe2+ and Mn2+, and NRAMP1, which participates in the resistance against infections and nutrient recycling. Despite previous studies contributing to our mechanistic understanding of the family, the structures of human SLC11 proteins and their relationship to functional properties have remained elusive. Here we describe the cryo-electron microscopy structures of DMT1 and NRAMP1 and relate them to their functional properties. We show that both proteins catalyze selective metal ion transport coupled to the symport of H+, but additionally also mediate uncoupled H+ flux. Their structures, while sharing general properties with known prokaryotic homologs, display distinct features that lead to stronger transition metal ion selectivity.